Safe water supply challenges for hand hygiene in the prevention of COVID-19 in Southern Nations, Nationalities, and People's Region (SNNPR), Ethiopia - Mekonnen Birhanie Aregu (Elsevier, 2021)
Background: Proper hand hygiene practices are critical in disease prevention and control, including preventing the spread of the COVID-19 pandemic, but according to a recent global report, three billion people lack access to basic hand washing facilities (soap and water) at home. Therefore, this study aimed to determine the challenges related to safe and adequate water provision for hand hygiene in the prevention of COVID-19 in Gedeo Zone, SNNPR, Ethiopia. Methods: An institutional-based cross-sectional study design was used to assess the challenges associated with safe water supply in the prevention of COVID-19 in Gedeo Zone. Simple random sampling was used. The water sector's challenges were assessed using in-depth interviews with key informants. Water samples were collected from hand washing stations using a sterile bottle and the standard tap water sampling procedure. Bacterial analysis was carried out using membrane filtration techniques. The Wagtech Palin test and the Delagua portable water testing kit procedure was used to analyze World Health Organization (WHO) critical physicochemical parameters. Result: The physicochemical analysis of the sample water from the hand washing facilities reveals that the pH (6.5–8) is within the WHO guideline in all samples except Gedeb town (11.1%). The residual chlorine in the samples was less than 0.2 mg/l, which is below the standard in all towns, but 15.8% of the samples in Wonago town were between 0.2–0.5mg/l. Faecal coliforms were not found in 27.5%, 21.0%, 16.6%, and 40.7% of the samples collected in Dilla, Wonago, Yirgachefe, and Gedeb town, respectively. The remaining samples were all positive for faecal coliforms. Unbalanced demand versus supply, inaccessibility, supply interruptions, financial constraints, a scarcity of competent human resources, a lack of regular water quality assessments, and a lack of stakeholder support were all identified as major challenges by all water sectors of the study towns. The majority of hand washing water samples from all of the study towns were bacteriologically unsafe. The water sector must work hard to ensure that the community has safe drinking water. All responsible bodies and potential stakeholders must support the water sectors in the Gedeo zone.